Remittances and the Dutch Disease in Sub-Saharan Africa: A Dynamic Panel Approach - Emmanuel Owusu-Sekyere; Reneé van Eyden; Francis M Kemegue (Contemporary Economics)
This paper investigates the effect of remittance inflows on real exchange rates in sub-Saharan Africa (SSA) using annual data from 1980 to 2008 for 34 countries, the method of moments estimator developed by Arellano and Bover (1995) and the feasible generalized least squares estimator developed by Parks (1967) and Kmenta (1986). We find that when cross-sectional dependence and individual effects are controlled for, remittances to sub-Saharan Africa as a whole increase the underlying real exchange rates of recipient countries. However, this real exchange rate appreciation is mitigated by monetary policy interventions and the direction of fiscal expenditures towards tradable goods. Thus, the real exchange rate appreciation does not lead to the loss of export competitiveness or a worsening of the trade deficit in the countries in the panel.